INTERPOLATION METHODS FOR SEA SURFACE HEIGHT MAPPING FROM ALTIMETRY SATELLITES IN INDONESIAN SEAS - Rossi Hamzah; Teguh Prayogo (National Institute of Aeronautics and Space of Indonesia (LAPAN), 2014)
Altimetry satellite data, has a very low spatial resolution for using in determine fishing ground area. With very low spatial resolution is required interpolation method that can mapped Sea Surface Height (SSH) with a good result. SSH data from Global Near Real Time from AVISO, mapped in geographic projection and interpolated with Inverse Distance Weighting (IDW) and Ordinary Krigging method. This interpolation method are expected to know which the good method for mapped SSH data in resulting better information. The results of statistical calculation shows that RMSE value and standar deviations from kriging method is smaller than IDW method.